1988
DOI: 10.1063/1.1139717
|View full text |Cite
|
Sign up to set email alerts
|

Wide temperature range IR spectroscopy cell for studies of adsorption and desorption on high area solids

Abstract: A new design for an infrared cell useful for studies of the spectrum of surface species on high area solids is presented. The cell is well suited over a wide temperature range (100–1000 K). Other demonstrated features of the cell include ultrahigh-vacuum operation, temperature control to ±1 K, linear and rapid temperature programmability and low-temperature gradients across the powdered sample. The method of sample preparation and support minimizes both heat and mass transport effects. A detailed literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
141
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(143 citation statements)
references
References 78 publications
0
141
0
2
Order By: Relevance
“…All of the FTIR spectroscopic experiments were conducted in transmission mode using a Bruker Tensor 27 spectrometer coupled to a batch-type catalytic reactor whose details have been described elsewhere [20,21]. All of the FTIR spectra were collected at 323 K. All of the adsorption/pre-treatment steps were also performed in batch mode.…”
Section: Instrumentationmentioning
confidence: 99%
“…All of the FTIR spectroscopic experiments were conducted in transmission mode using a Bruker Tensor 27 spectrometer coupled to a batch-type catalytic reactor whose details have been described elsewhere [20,21]. All of the FTIR spectra were collected at 323 K. All of the adsorption/pre-treatment steps were also performed in batch mode.…”
Section: Instrumentationmentioning
confidence: 99%
“…The adsorbed CH 2 Br 2 amount continues to decrease after the surface is heated to 150 • C. New bands appear at 1367, 1387, 1557, 2841, and 2936 cm −1 . Based on the similar frequencies observed in the previous studies of dissociative adsorption of formic acid and methanol on TiO 2 , the first three bands are assigned to -COOsymmetric stretching, CH bending, and -COO-antisymmetric stretching of adsorbed HCOO and the last two are assigned to symmetric and antisymmetric CH 3 The adsorption of CH 2 Br 2 causes absorption changes over 3200 cm −1 . The negative bands in the 3600-3800 cm −1 region signify loss of isolated surface OH groups and the appearance of the broad band in the 3200-3600 cm −1 region reveals the formation of hydrogen bonding.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the stainless steel IR cell with two CaF 2 windows for IR transmission down to 1000 cm −1 used in the present study has been reported previously [3]. In our system, the IR cell was † E-mail: jonglin@mail.ncku.edu.tw connected to a gas manifold which was pumped by a 60 L/s turbomolecular pump with a base pressure of ∼ 1 × 10 −7 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…22,35 As described previously, the tungsten grid was clamped onto two copper bars attached to the copper wires of a vacuum feedthrough at the base of a dewar used to hold liquid nitrogen or acetone/dry ice for cooling. 36 Heating was supplied to the sample by passing a current through the tungsten grid. The temperature was sensed by a K-type thermocouple spot-welded to the grid, and temperature was controlled by the a home-built proportional-integral-derivative (PID) controller, which maintained the temperature within 1 K and was programmed to the ramp the temperature at 4 K/s during temperature changes.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%